Efek mediasi employee engagement terhadap manajemen konflik dan kinerja karyawan pada perusahaan keluarga - Fazza, Diniar Mufrihatul; Padmalia, Metta; Antonio, Tony (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2024)
This study aims to explore the mediating effect of employee engagement on conflict management and employee performance in family business. The study distributed surveys to the staff of family business, namely hospital. The data were then analyzed using the SEM-PLS (Structural Equation Modeling - Partial Least Squares) method. The findings of this study confirm that conflict management has a positive and significant influence on employee engagement. Additionally, employee engagement also significantly and positively affects employee performance. Furthermore, these findings affirm that employee engagement serves not only as a result of effective conflict management but also as a mediating factor that strengthens the relationship between conflict management and employee performance.